The Impact of Modifiable Risk Factors on the Endothelial Cell Methylome and Cardiovascular Disease Development - Hashum Sum; Alison C. Brewer (Frontiers in Bioscience-Landmark)
Cardiovascular disease (CVD) is the most prevalent cause of mortality and morbidity in the Western world. A common underlying hallmark of CVD is the plaque-associated arterial thickening, termed atherosclerosis. Although the molecular mechanisms underlying the aetiology of atherosclerosis remain unknown, it is clear that both its development and progression are associated with significant changes in the pattern of DNA methylation within the vascular cell wall. The endothelium is the major regulator of vascular homeostasis, and endothelial cell dysfunction (ED) is considered an early marker for atherosclerosis. Thus, it is speculated that changes in DNA methylation within endothelial cells may, in part, be causal in ED, leading to atherosclerosis and CVD generally. This review will evaluate the extensive evidence that environmental risk factors, known to be associated with atherosclerosis, such as diabetes, metabolic disorder, smoking, hypertension and hypercholesterolaemia etc. can affect the methylome of the endothelium and consequently act to alter gene transcription and function. Further, the potential mechanisms whereby such risk factors might impact upon the activities and/or specificities of the epigenetic writers and erasers which determine the methylome [the DNA methyl transferases (DNMTs) and Ten Eleven translocases (TETs)] are considered here. Notably, the TET proteins are members of the 2-oxoglutarate-dependent dioxygenase superfamily which require molecular oxygen (O2) and α-ketoglutarate (α-KG) as substrates and iron-2+ (Fe II) as a cofactor. This renders their activities subject to modulation by hypoxia, metabolic flux and cellular redox. The potential significance of this, with respect to the impact of modifiable risk factors upon the activities of the TETs and the methylome of the endothelium is discussed.